PENGARUH DEWAN KOMISARIS INDEPENDEN, KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS DAN LEVERGE TERHADAP TAX AVOIDANCE - Riko Ariawan, I Made Agus; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
This study aimed to demonstrate empirically the influence of independent board, institutional ownership, profitability and leverage against tax avoidance in the service sector companies in the Stock Exchange 2012- 2014. The theory used in this research is the theory of the Agency (Agency Theory), Theory of Compliance and Accounting Theory Positive. The population used in this study are all companies listed on the Stock Exchange the period of 2012- 2014 as many as 268 companies. The samples in this study using the purposive sampling method. The data collection is done by dokumentasi. Data analysis used is multiple linear regression analysis. The results this research showed that the independent board have negatively affect the profitability of tax avoidance. Institutional ownership variable and leverage have  positive effect on tax avoidance.
Keywords: independent commissioners, institutional ownership, profitability, leverage